Rules Enforcement And Unethical Behavior: Empirical research on Employee Fraud in Local Government Agencies - Dekeng Setyo Budiarto; Yona Setyoningtyas (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2019)
The tendency of fraud is one of the major threats to Indonesian country. The current research aims to study the effect of rules enforcement and unethical behaviors on the tendency of fraud based on gender. The sample consists of 126 employees from 28 Local Government Agencies (LGAs) in Kulon Progo regency. Purposive sampling was the sampling technique employed in this study. The results demonstrated a significant effect of unethical behavior on the tendency of fraud. However, rules enforcement level has no significant effect on the tendency of fraud. In addition, gender differences were observed in unethical behavior and the tendency of fraud. On the other hand, gender differences were not present in the level of rules enforcement.